Complex odontoma restricting mouth opening: an unusual clinical presentation and surgical management - Torres Augusto-Neto, Renato; Marinheiro, Bruno Henrique; Silveira, Heitor Albergoni; Jimenez Polanco, Xiomara Beatriz; Esquiche León, Jorge; Trivellato, Alexandre Elias; Edvard Sverzut, Cassio (International Journal of Health Sciences, 2021)
Odontomas are common benign odontogenic tumors, being often detected on routine radiographs during the first two decades of life. Rarely, odontoma can interfere with jaw movements, causing mouth opening limitation. A 28-year-old male patient was referred complaining of restriction of mouth opening and mandibular movements, which started 6 months ago. Clinical examination revealed a painless increase of volume on the right maxilla, which interfered the mandibular movements, being associated with pain in these attempts. A well-defined, oval radiopaque lesion in close relationship with the impacted maxillary right third molar was detected in tomographic reconstructions. A surgical excision of the lesion was performed, and microscopy revealed complex odontoma. After 4 months of follow-up, the patient achieved adequate mouth opening and recovered mandibular movements. In the current case, the lesion was placed in a difficult access site, which directly interfered with the displacement of coronoid process.